Prognostic factors for lung function in systemic sclerosis: prospective study of 105 cases - Gilson, M; Zerkak, D; Wipff, J; Dusser, D; Dinh-Xuan, A T; Abitbol, V; Chaussade, S; Legmann, P; Kahan, A; Allanore, Y (The European respiratory journal, 2010)
The aims of the present study were to identify prognostic factors for systemic sclerosis (SSc)-related interstitial lung disease and to clarify the possible causative role of manometric oesophageal involvement. Consecutive SSc patients underwent pulmonary function tests and oesophageal manometry. They were included in the study if pulmonary function tests were repeated >12 months after baseline. The primary end-point was a decrease of >or=10% of the predicted value in forced vital capacity (FVC). The secondary end-points were a decrease of >or=15% pred in lung carbon monoxide diffusing capacity (D(L,CO)) and a decrease of >or=20% pred in FVC. Of the 105 patients (45 diffuse SSc; median disease duration 2.0 yrs), 23 (23%) had a FVC of <80% pred, 60 (59%) had a D(L,CO) of <80% pred and 57 (54%) showed severe oesophageal hypomotility at baseline. Over 72+/-46 months, 29 (28%) patients displayed a decrease of >or=10% pred in FVC, 39 (40%) of 98 patients displayed D(L,CO) decline and 19 (18%) patients displayed a decrease of >or=20% pred in FVC. On multivariate analysis, diffuse SSc was a significant predictor for a decrease of >or=10% pred in FVC (p = 0.01). No other predictor of a decrease in pulmonary function was identified. Only diffuse SSc was predictive of a decrease in pulmonary function in this early-SSc cohort. This does not support preliminary data suggestive of a causative role of oesophageal involvement.